Isolation, Characterization and Biotechnological Potentials of Thraustochytrids from Icelandic Waters - Stefánsson, Magnús Örn; Baldursson, Sigurður; Magnússon, Kristinn P.; Eyþórsdóttir, Arnheiður; Einarsson, Hjörleifur (Marine Drugs, 2019)
The following study reports on the first thraustochytrid isolates identified from Iceland. They were collected from three different locations off the northern coast of the country (Location A, Skagaströnd; Location B, Hveravík; and Location C, Eyjafjörður). Using 18S rDNA sequence analysis, isolates from Locations A and B were identified within the Thraustochytrium kinnei species while other isolates within the Sicyoidochytrium minutum species when compared to other known strains. Cells isolated from Locations A ([Formula: see text] g/L) and B ([Formula: see text] g/L) produced more biomass than the ones isolated from Location C ([Formula: see text] g/L). This study offers the first-time examination of the utility of byproducts from fisheries as a nitrogen source in media formulation for thraustochytrids. Experiments showed that isolates produced more biomass (per unit of substrate) when cultured on nitrogen of marine ([Formula: see text] g/L) as compared to of commercial origin ([Formula: see text] g/L). Glycerol ([Formula: see text] g/L) was a better carbon source than glucose ([Formula: see text] g/L) in growth studies. Fatty acid (FA) profiles showed that the isolates from Location C (S. minutum) had low ratios of monounsaturated ([Formula: see text]) and omega-6 ([Formula: see text]) FAs. However, the isolates also had high ratios of docosahexaenoic acid (DHA; [Formula: see text]) and total omega-3 FAs ([Formula: see text]), indicating that they could serve as a source of marine oils for human consumption and in aquaculture feeds. The T. kinnei isolates from Location A could be used in biodiesel production due to their high ratios of monounsaturated ([Formula: see text]) long chain ([Formula: see text]) FAs.